Characterizing the Duration and Severity of Fishing Gear Entanglement on a North Atlantic Right Whale (Eubalaena glacialis) Using Stable Isotopes, Steroid and Thyroid Hormones in Baleen - Lysiak, Nadine S. J.; Trumble, Stephen J.; Knowlton, Amy R.; Moore, Michael J. (Frontiers in Marine Science, 2018)
North Atlantic right whales (Eubalaena glacialis) are highly endangered and frequently exposed to a myriad of human activities and stressors in their industrialized habitat. Entanglements in fixed fishing gear represent a particularly pervasive and often drawn-out source of anthropogenic morbidity and mortality to the species. To better understand both the physiological response to entanglement, and to determine fundamental parameters such as acquisition, duration, and severity of entanglement, we measured a suite of biogeochemical markers in the baleen of an adult female that died from a well-documented chronic entanglement in 2005 (whale Eg2301). Steroid hormones (cortisol, corticosterone, estradiol, and progesterone), thyroid hormones (triiodothyronine (T3) and thyroxine (T4)), and stable isotopes (δ13C and δ15N) were all measured in a longitudinally sampled baleen plate. This yielded an 8-year profile of foraging and migration behavior, stress response, and reproduction. Stable isotopes cycled in annual patterns that reflect the animal’s north-south migration behavior and seasonally abundant zooplankton diet. A progesterone peak, lasting approximately 23 months, was associated with the single known calving event (in 2002) for this female. Estradiol, cortisol, corticosterone, T3, and T4 were also elevated, although variably so, during the progesterone peak. This whale was initially sighted with a fishing gear entanglement in September 2004, but the hormone panel suggests that the animal first interacted with the gear as early as June 2004. Elevated δ15N, T3, and T4 indicate that Eg2301 potentially experienced increased energy expenditure, significant lipid catabolism, and thermal stress approximately three months before the initial sighting with fishing gear. All hormones in the panel (except cortisol) were elevated above baseline by September 2004. This novel study illustrates the value of using baleen to reconstruct recent temporal profiles and as a comparative matrix in which key physiological indicators of individual whales can be used to understand the impacts of anthropogenic activity on threatened whale populations.